RESEÑA de: Gómez-Lara, Manuel J.; Mora, M.ª José; Pando, Laura de; Portillo, Rafael; Prieto-Pablos, Juan y Vélez Núñez, Rafael (Eds.). "Restoration Comedy, 1660-1670: a Catalogue". Youngstown, New York: Teneo Press, 2014. ISBN: 978-1-934844-84-7 - Ballesteros González, Antonio (Epos : Revista de filología, 2016)
-